Sistema de monitoramento remoto de temperatura para aplicação em experimento de determinação da difusividade térmica em alimentos - Martins, Matheus Protasio (2022)
In this work, the improvement project and consequent modification of an electronic device for monitoring thermal diffusivity in foods was carried out. The determination of thermal diffusivity is of paramount importance for food preservation. To obtain this magnitude, it is necessary to submit the material to be analyzed to a thermal experiment. Among them, the Dickerson method is a widely used method that consists of immersing a sample of food in a thermal bath, whose control is performed manually. In order to automate this process and make it less prone to errors, Souto developed a device using a Raspberry Pi 3 to facilitate this process. However, your device requires an Ethernet cable and Internet connection to function properly. To optimize the device developed by Souto, this work proposes to refactor the control hardware, increase the practicality and present a friendly interface to the user. For this, a control device was developed with an ESP32 in C/C++ programming language and a control application with React Native, a JavaScript framework. The ESP32, which measures and transmits data from thermocouple sensors which are sent via Bluetooth to the cell phone application. In this way, it is possible to monitor and control the instantaneous measurement of the sensors through the interface on the cell phone. At the end of the development, it can be verified that the resulting device proved to be effective to assist in the process of obtaining data for the calculation of diffusivity and a decrease in the cables in the device, in addition to making the monitoring remote.